2021
DOI: 10.4103/aca.aca_120_19
|View full text |Cite
|
Sign up to set email alerts
|

Thrombus in transit across a patent foramen ovale in a patient with cerebrovascular accidents, pulmonary embolism, and deep vein thrombosis

Abstract: The diagnosis of paradoxical emboli remains elusive in many cases. The causal association between the thrombotic source, the intracardiac shunt, and the final emboli location is seldom demonstrated. We present the case of a 42-year-old woman admitted to the hospital with a third stroke. The presence of a thrombus in transit through a patent foramen ovale (PFO), a deep vein thrombosis (DVT), bilateral pulmonary emboli, and an acute cerebral infarct were concurrently documented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Fauveau et al reported 88 cases of entrapped thrombus in PFO in a literature review and self-examination and found that 44% of patients with paradoxical embolism and the most frequent site of systemic embolism was cerebral [ 5 ]. Geltes et al also reported a case of thrombus in transit across a PFO complicating DVT and PE, which was discovered after a prior cerebral embolism, and was successfully treated by surgical embolectomy with closure of the PFO [ 10 ]. Therefore, they concluded that surgical treatment appears justified in the prevention of paradoxical embolism and must be performed without delay if it is the preferred treatment strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Fauveau et al reported 88 cases of entrapped thrombus in PFO in a literature review and self-examination and found that 44% of patients with paradoxical embolism and the most frequent site of systemic embolism was cerebral [ 5 ]. Geltes et al also reported a case of thrombus in transit across a PFO complicating DVT and PE, which was discovered after a prior cerebral embolism, and was successfully treated by surgical embolectomy with closure of the PFO [ 10 ]. Therefore, they concluded that surgical treatment appears justified in the prevention of paradoxical embolism and must be performed without delay if it is the preferred treatment strategy.…”
Section: Discussionmentioning
confidence: 99%